De l’émotion à l’émotion - Gilbert Elbaz (Études Caribéennes)
The present article opens the issue of Etudes Caribéennes dedicated to the study of social movements and analyzes the theoretical significance of emotion within the emergence and maintenance of these sociological phenomena. Rejected by classical theorists as dangerous aberration, emotion will be consecutively reintegrated by neo-classical theorists, then once again rejected by modern rationalists or ignored by constructivists, and finally totally reintegrated, even centered within the theoretical framework adopted by certain contemporary post-modern sociologists. Contributions to this issue of Etudes Caribéennes reflect the new strides made by emotion within the integrative post-modern theory of social movements.